Standardized standards and their relationship with performance in unidocent schools of Combarbalá, Coquimbo region-Chile - Muñoz Pérez, Guillermo Andrés (2024)
The main objective of this research was to determine the relationship between standardized norms and performance in single-teacher schools in Combarbalá, Coquimbo Region-Chile, year 2020. The work methodology used was developed through the quantitative approach in a type of basic research with a non-experimental-correlational design. The population consisted of 20 teachers where a Likert-type scale questionnaire was used to collect information. Consequently, the instrument was validated through expert judgments and the reliability used through Cronbach's Alpha with a value of 0.93 for the standardized norms variable and 0.93 for the performance variable in single-teacher schools, being reliably considered “Very High". To obtain the correlation between the variables,  de rho de Pearson test was used. The study showed that there is a direct and significant relationship between standardized norms and performance in single-teacher schools, with a correlation of 0.231 and a confidence level of 95%.